Regulation of immune microenvironments by polyetheretherketone surface topography for improving osseointegration - Yuqing Zhao; Yanxin An; Fan Wu; Lipeng Liu; Franklin R. Tay; Yang Jiao; Jing Wang (Journal of Nanobiotechnology)
Abstract Optimizing the immune microenvironment is essential for successful implant osseointegration. In this study, four different nano/microstructures were fabricated on polyetheretherketone (PEEK) substrates by varying the agitation speed during sulfonation to influence osteoimmunomodulation and implant integration. The results indicate that nano/microstructures with minimal dimensions (SP450) inhibit actin polymerization by reducing calcium influx through PIEZO1, activating the anti-inflammatory M2 macrophage phenotype. Among the tested specimens, SP450 exhibited the lowest expression levels of tumor necrosis factor-α and interleukin-1β while releasing the highest levels of anti-inflammatory factors, including interleukin-4 and interleukin-10. This optimized immune environment promotes the osteogenesis of MC3T3-E1 pre-osteoblasts and enhances the osseointegration of PEEK implants. Transcriptomic analysis and validation experiment further revealed that SP450 inhibits osteoclastic differentiation by down-regulating transforming growth factor-β2 and suppressing the NF-κB signaling pathway. These findings suggest that manipulating the surface topography of PEEK implants is an effective strategy for enhancing osseointegration with promising clinical applications.